Evaluation of some organic compounds on bloodstream forms of Trypanosoma cruzi - João S. Silva; S. Ferrioli-Filho; M. M. Kanesiro; V. F. Ferreira; S. C. Santos; C. N. Pinto; J. L. Fonseca; H. E. Mizrahy; B. Gilbert; M. C. F. R. Pinto; F. W. Ribeiro; A. V. Pinto (Memorias do Instituto Oswaldo Cruz, 1992)
Accidental transmission of Chagas' disease to man by blood transfusion is a serious problem in Latin-America. This paper describes the testing of several synthetic, semi-synthetic, and natural compounds for their activity against blood trypomastigotes in vitro at 4-C. The compounds embody several types of chemical structures: benzoquinone, naphthoquinone, anthracenequinone, phenanthrenequinone, imidazole, piperazine, quinoline, xanthene, and simple benzenic and naphthalenic derivates. Some of them are for the first time tested against Trypanosoma cruzi. The toxic effect these compounds on this parasite was done by two quite distinct sets of experiments. In one set, the compounds were added to infected blood as ethanolic solution. In this situation the most active one was a furan-1, 2-naphthoquinone, in the same range as gentian violet, a new fact to be considered in the assessment of structure-activity relationships in this class of compounds. In other set, we tentatively evaluated the biological activity of water insoluble compounds by adding them in a pure form without solvent into infected blood. In this way some appear to be very active and it was postulated that the effectiveness of such compounds must result from interactions between them and specific blood components.